The effects of climate change on water resources in north-eastern Morocco, the case of Berkane city - Benasquar, Mustapha; Ghazi, AbdelKhalek; Ahroud, AbdelWahed; Buabid, Noureddine (Journal of natural sciences, life and applied sciences, 2023)
The world today faces many challenges, one of them is the climate change which has become one of the issues that receive increasing attention globally, due to its disastrous effects at all life fields, and this is due to human factors, including the southern bank of the Mediterranean, especially in Berkane city in a center of Trifa plain , in the northeast of Morocco, which is one of the most important irrigated areas in the country due to its great contribution to agricultural production and its reliance on achieving economic and social development in the region. However, its climate during the last six decades has witnessed clear variations in the rates of precipitation and temperature, be it annual or monthly, or even seasonal and daily. This increases the severity of the climatic drought, which in turn affects water resources. Therefore, it is imperative that great efforts must be made to limit the effects of these changes due to the excessive depletion of water in the agricultural sector. Through this intervention, we aim to highlight the climatic changes that occurred on the Berkane city, and their repercussions on its water resources, and how to adapt these changes to achieving sustainable development for the studied area.